2021
DOI: 10.1111/ppc.12857
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anxiety levels of hospitalized COVID‐19 patients, individuals under quarantine, and individuals in society

Abstract: Purpose This study aims to compare the anxiety levels of COVID‐19 patients, individuals under quarantine, and healthy individuals in society. Design and Methods This cross‐sectional study was conducted from May 25, 2020 to June 25, 2020 in a city located in the northwest of Turkey. The data were collected using a personal information form, the Beck Anxiety Scale, administered in face‐to‐face interviews, and online questionnaires. The data were analyzed using descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
(94 reference statements)
1
13
0
Order By: Relevance
“…; and in those who had been diagnosed with COVID‐19 in the study conducted by Tokur Kesgin et al . The findings of this study are parallel with the findings reported in these studies 18,20–22 …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…; and in those who had been diagnosed with COVID‐19 in the study conducted by Tokur Kesgin et al . The findings of this study are parallel with the findings reported in these studies 18,20–22 …”
Section: Discussionsupporting
confidence: 91%
“…A study in the literature also reported that individuals with higher education levels experienced higher anxiety levels. 18 The study conducted by Cybulski et al 19 reported no significant relationships between older individuals' anxiety and education level.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations